Lead(II) Siloxides. Issue 71 (21st November 2019) - Someşan, Adrian‐Alexandru; Le Coz, Erwann; Raţ, Ciprian Ionuţ; Dorcet, Vincent; Roisnel, Thierry; Silvestru, Cristian; Sarazin, Yann
Abstract: Although Pb II ‐siloxides have been known until now to decompose to oxoclusters, here [RO F PbOSi(SiMe3 )3 ] (RO F =fluoroalkoxide) and, most importantly, [Pb2 OSi(SiMe3 )3 μ2 ‐OSi(SiMe3 )3 3 ], are presented. The unusual bonding pattern in the latter thermally stable dinuclear complex was investigated by crystallographic and computational methods. Its stability is much higher than that of the simple, yet elusive "[Pb(OSiPh3 )2 ]", for which decomposition pathways towards [Pb4 (μ4 ‐O)(μ2 ‐OSiPh3 )6 ] have been clearly established. Abstract : Stable lead(II) siloxides that do not decompose to oxoclusters have been prepared. These include the first homoleptic Pb II ‐siloxide, which also exhibits unique structural features.